GATS and the regulation of international trade in services / edited by Marion Panizzon, Nicole Pohl and Pierre Sauvé. - Panizzon, Marion; Pohl, Nicole, 1974-; Sauvé, Pierre, 1959- (Cambridge University Press, 2008)
This collection of essays takes stock of the key challenges that have arisen since the entry into force of the General Agreement on Trade in Services in the mid-1990s and situates them in the context of the WTO's Doha Development Agenda and the proliferation of preferential agreements addressing services today. The multidisciplinary approach provides an opportunity for many of the world's leading experts and a number of new analytical voices to exchange ideas on the future of services trade and regulation. Cosmopolitan approaches to the treatment of labour mobility, the shape of services trade disciplines in the digital age and pro-competitive regulation in air transport are explored with a view to helping readers gain a better understanding of the forces shaping the changes. An essential read for all those concerned with the evolution of the rules-based trading system and its impact on the service economy.